Do climate shocks disadvantage household investment in human capital in Benin? An approach based on the endogenous treatment regression model - Logozo, Christian Duhamel; Kougblenou Menou, Vihoutou Médjikouê Marthe; Hekponhoue, Sylvain (European Scientific Journal, ESJ, 2024)
The increasing number of drought and flood shocks in Benin is causing considerable economic losses and social disruption. This article looks specifically at the effects of these shocks on household human capital expenditure in Benin’s three climatic zones, to highlight the effects specific to each zone. The data used come from the Harmonized Survey of Household Living Conditions. A linear regression model of the endogenous treatment is used for the analyses. Findings indicate that climate shocks reduce household capital expenditure and that this impact depends on the household’s climatic zone of residence. Investment in resilience infrastructure is suggested, as is a policy of social assistance to disaster-stricken households.